2009
DOI: 10.1063/1.3116504
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in HBr and Ar cure plasma treatments applied to 193 nm photoresists

Abstract: In this article, we have performed detailed investigations of the 193 nm photoresist transformations after exposure to the so-called HBr and Ar plasma cure treatments using various characterization techniques (x-ray photoelectron spectroscopy, Fourier transformed infrared, Raman analyses, and ellipsometry). By using windows with different cutoff wavelengths patched on the photoresist film, the role of the plasma vacuum ultraviolet (VUV) light on the resist modifications is clearly outlined and distinguished fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 36 publications
6
53
0
Order By: Relevance
“…19 The 193 nm photoresist studied in this work is IM5010 commercial resist from Dow Electronic Materials whose chemical structure is close to poly(methyl methacrylate) (PMMA) derived polymer with several pending groups such as adamantyl methacrylate for the leaving group, alphagamma butyrolactone methacrylate for the solubility and a polar group. 19 Two types of substrates have been used: 130 nm thick photoresist films coated on silicon substrate and photoresist patterns printed by 193 nm lithography on 35 nm Si-ARC/ 200 nm SOC hard mask/Si bulk stack. The patterns studied here are isolated lines with height of 120 nm and width of 70 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The 193 nm photoresist studied in this work is IM5010 commercial resist from Dow Electronic Materials whose chemical structure is close to poly(methyl methacrylate) (PMMA) derived polymer with several pending groups such as adamantyl methacrylate for the leaving group, alphagamma butyrolactone methacrylate for the solubility and a polar group. 19 Two types of substrates have been used: 130 nm thick photoresist films coated on silicon substrate and photoresist patterns printed by 193 nm lithography on 35 nm Si-ARC/ 200 nm SOC hard mask/Si bulk stack. The patterns studied here are isolated lines with height of 120 nm and width of 70 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In previous articles, [19][20][21] we studied the impact of HBr plasma treatment and the role of the vacuum ultra violet (VUV) light emitted by the HBr plasma on the chemical modifications and resulting roughness of 193 nm photoresists. We have shown that both HBr plasma and VUV light treatments lead to similar resist bulk chemical modifications that favors resist surface roughness smoothening.…”
Section: Introductionmentioning
confidence: 99%
“…poly͑methyl methacrylate͒ ͑PMMA͒, 8 193 and 248 nm photoresists 5,6,9,10 ͔ and has been described as a thin, highly crosslinked and graphitized layer. [4][5][6][11][12][13][14][15][16] We have previously shown that under energetic Ar + ion bombardment during plasma etching, a dense, amorphous carbonlike modified layer is formed at the surface of a wide range of polymers ͓polystyrene ͑PS͒, poly͑␣-methylstyrene͒, poly͑4-methylstyrene͒, PMMA, poly͑hydroxyadamantyl acrylate͒, and poly͑hydroxyadaman-tyl methacrylate͔͒ with a thickness of a few nanometers. 17 This modified layer forms within the first few seconds of plasma exposure ͑corresponding to an ion fluence ϳ4 ϫ 10 16 cm −2 ͒, concurrent with a period of rapid surface roughening.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the HBr-containing plasmas have been successfully applied for the highly-anisotropic etching of both single crystal and poly-Si because of the negligible spontaneous reaction between Br and Si [3,4]. And finally, the HBr-rich plasmas provide much lower (compared with the Cl-containing plasmas) etch rates of organic photoresists (PR) due to the graphitization and the cross-linking of the PR film caused by the UV (*110-210 nm) irradiation from the excited HBr molecules [5,6]. Unfortunately, the most of existing works discuss only the effects of main operating parameters (gas pressure, input power, bias power and gas mixing ratio) on the etch rate and related characteristics while the relationships between plasma parameters, plasma composition and etch kinetic have received much less attention.…”
mentioning
confidence: 99%